Topical minocycline microspheres versustopical chlorhexidine gel as an adjunct to mechanical debridement of incipient peri-implant infections: a randomized clinical trial - Stefan Reichert (journal of clinical periodontology, 2006)
Aim: This randomized clinical trial presents a 12-month follow-up of the clinical and microbiological results after application of minocycline microspheres as an adjunct to mechanical treatment of incipient peri-implant infections compared with an adjunctive treatment using 1% chlorhexidine gel application. Material and Methods: Thirty-two subjects with probing depth X4 mm, combined with bleeding and/or exudate on probing and presence of putative pathogenic bacteria were given oral hygiene instructions and mechanical treatment of infected areas adjacent to implants. The subjects were then randomly assigned adjunctive subgingival antimicrobial treatment using either chlorhexidine gel or minocycline microspheres. Sixteen patients in the minocycline group and 14 in the chlorhexidine group completed the study. Follow-up examinations were carried out after 10 days, 1, 2, 3, 6, 9 and 12 months. Results: The adjunctive use of minocycline microspheres resulted in improvements of probing depths and bleeding scores, whereas the adjunctive use of chlorhexidine only resulted in limited reduction of bleeding scores. For the deepest sites of the treated implants in the minocycline group, the mean probing depth was reduced from 5.0 to 4.4mm at 12 months. This study could not show any significant difference in the levels of bacterial species or groups at any time point between the two antimicrobial agents tested. The present findings encourage further studies on adjunctive use of minocycline microspheres in the treatment of peri-implant lesions. Conclusions: The use of a local antibiotic as an adjunct to mechanical treatment of incipient peri-implantitis lesions demonstrated improvements in probing depths that were sustained over 12 months.